Multi-Stage Data Envelopment Analysis to Evaluate Inclusive-Based Elementary Schools in Indonesia - chamdani, muhamad (The Journal of Educational Development, 2019)
The main purpose of this study is to evaluate inclusive-based elementary schools in Indonesia by measuring the technical efficiency of these schools. Data envelopment analysis (DEA) was used to obtain the efficiency scores where there were two popular models; CRS and VRS model. As many as 38 primary schools in Central Jakarta in Indonesia in the period 2014/2015 were determined as decision making units (DMUs) with six inputs and four outputs. The results revealed that CRS (constant returns to scale) model produced as many as 9 schools with efficient performances while VRS (variable returns to scale) model produced as many as 25 schools that performed efficiently whereas there were 12 schools (31.58 percent) had the efficiency scores below the average scores for both CRS and VRS models. Further, the average scores of CRS and VRS models were 0.819 and 0.869, respectively. Overall, elementary schools which implemented inclusive education in Central Jakarta are suggested to improve their performances.